A Manajemen Fisioterapi pada Suspek Gout Arthritis : Laporan Kasus - Mustari, Yery; Putri, Melda; Sarira, Christine Milenia; Suciawati, Suciawati; Amiruddin, Rezky Awalia; Nooraini, Fahira Azzahra; Sari, Noorindah; Yusri, Putri Ayuninda; Athaya, Pritha Qurratul Aini; Syawal, Akram Ibnu; Martono, Anna Rahma; Agung, Nurdeli Wasi; et al. (Jurnal Fisioterapi dan Rehabilitasi; Vol 8 No 2 (2024): Jurnal Fisioterapi dan RehabilitasiDO - 10.33660/jfrwhs.v8i2.382, 2024)
One of the most common musculoskeletal problems is joint arthritis. Arthritis is usually associated with diseases of the elderly. However, arthritis can also affect the younger population. One of the joint arthritis is gout arthritis. Gouty arthritis is an inflammatory condition of the joints caused by deposits of monosodium urate (MSU) crystals in the joints. MSU is the end product of purine metabolism in the body. This condition can cause pain and stiffness in the joints, swelling, limited range of motion (ROM), and impaired Activity Daily Living ( ADL ) and if not given proper treatment can cause joint deformity. This case report contains physiotherapy management of a case of suspected gouty arthritis in a 26 year old woman with the main complaint of pain, stiffness and swelling in the left ankle. After receiving physiotherapy intervention, there were positive results in the form of reduced pain and swelling, as well as increased ROM. This report also contains the patient's clinical presentation as well as literature supporting physiotherapy management of gout arthritis.